2018
DOI: 10.1080/10717544.2018.1474968
|View full text |Cite
|
Sign up to set email alerts
|

SPECT/CT imaging of chemotherapy-induced tumor apoptosis using 99mTc-labeled dendrimer-entrapped gold nanoparticles

Abstract: Non-invasive imaging of apoptosis in tumors induced by chemotherapy is of great value in the evaluation of therapeutic efficiency. In this study, we report the synthesis, characterization, and utilization of radionuclide technetium-99m (99mTc)-labeled dendrimer-entrapped gold nanoparticles (Au DENPs) for targeted SPECT/CT imaging of chemotherapy-induced tumor apoptosis. Generation five poly(amidoamine) (PAMAM) dendrimers (G5.NH2) were sequentially conjugated with 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 33 publications
3
29
0
Order By: Relevance
“…Instant thin layer chromatography (ITLC) was used to analyze the labeling efficiency and radiostability of the 131 I‐labeled materials. The efficiency of 131 I labeling onto PNS.NHAc‐HPAO‐PS and PEI.NHAc‐HPAO‐PS was determined to be 76.05 ± 3.75% and 55.3 ± 1.13%, respectively, which are comparable to those reported in the literature . In other words, the doses of PNS.NHAc‐HPAO( 131 I)‐PS and PEI.NHAc‐HPAO( 131 I)‐PS were presented as 2.81 and 2.03 MBq µg −1 , respectively.…”
Section: Resultssupporting
confidence: 79%
“…Instant thin layer chromatography (ITLC) was used to analyze the labeling efficiency and radiostability of the 131 I‐labeled materials. The efficiency of 131 I labeling onto PNS.NHAc‐HPAO‐PS and PEI.NHAc‐HPAO‐PS was determined to be 76.05 ± 3.75% and 55.3 ± 1.13%, respectively, which are comparable to those reported in the literature . In other words, the doses of PNS.NHAc‐HPAO( 131 I)‐PS and PEI.NHAc‐HPAO( 131 I)‐PS were presented as 2.81 and 2.03 MBq µg −1 , respectively.…”
Section: Resultssupporting
confidence: 79%
“…In our recent work, we developed CTX-conjugated multifunctional dendrimers labeled with radionuclides for targeted imaging and therapy of glioma [38]. Furthermore, we have demonstrated that radionuclide-labeled dendrimers can be used to entrap gold nanoparticles (Au NPs) for tumor dual mode imaging applications, such SPECT/CT and SPECT/MR imaging [3941]. The previous successes of dendrimer-based multifunctional nanosystems and the unique biological properties of CTX, prompted our investigation of dendrimers as a BBB-penetrating nanoplatform for the dual mode imaging and radionuclide therapy of glioma.…”
Section: Introductionmentioning
confidence: 99%
“…Duramycin has a high specificity in recognizing the phospholipid phosphatidylserine (PS), which is present on the outer surface of the cellular membrane of apoptotic cells. The results show that SPECT images of apoptotic C6 cells treated with the 99mTc-duramycin-Au DENPs are much brighter than those of apoptotic C6 cells treated with the 99m Tc-duramycin-Au DENPs [128].…”
Section: In Vitro Evaluation Of Radionuclides Delivered By Aunps and mentioning
confidence: 91%
“…A recent study aimed to evaluate the synthesis, characterization, and use of 99m Tc-labeled dendrimer-entrapped AuNPs ( 99m Tc-Au DENPs) for targeted SPECT/CT imaging of chemotherapy-induced tumor apoptosis [128]. Indeed, 99m Tc-Au DENPs allowed the targeted imaging of apoptotic cancer cells in vitro and of tumor apoptosis after doxorubicin treatment in nude mice bearing C6 glioma cells and xenografted tumors.…”
Section: Integrin V 3-based Targetingmentioning
confidence: 99%